Measuring Neighbourhood Hardships and NeighbourhoodChange between 2010-2015 in Suburban Neighbourhoods of Buffalo Metropolitan Area, New York - Saleh, Ilhamdaniah (Geographica Pannonica, 2021)
Neighbourhoodsin urban and suburban areasexperienced changes in terms of physical, social, economic, and demographics. Neighbourhood Hardship Index (NHI) had been used to measure neighbourhood socio-economic condition, using various census variables. Suburban neighbourhoodswhich underwent a change lead to stratification into striving outersuburbs and declining innersuburbs. The context of this study was suburban neighbourhoods in Buffalo Metropolitan Area (BMA), New York. This paper aimed at highlighting spatial variability of neighbourhood change in inner- and outer-suburban neighbourhoods of BMA between 2010-2015. This study examined factors that significantly contribute to neighbourhood change. Also, this study examined whether there a difference in the change of neighbourhood hardship index between inner- and outer-suburban neighbourhoods. Composite NHI was developed from economic, demographic, and housing variables. Neighbourhood change was measured by comparing the composite NHI 2010 with that of 2015. The findings depicted a variation of change in hardships index across suburban neighbourhoods. Neighbourhoods with higher hardship index were primarily located in innersuburbs. Policy implications call for concerted efforts to tackle the decline in the economy, education, demography to promote equity across neighbourhoods in suburban areas.